Interactions between genes involved in physiological dysregulation and axon guidance: role in Alzheimer’s disease - Arbeev, Konstantin G.; Ukraintseva, Svetlana; Bagley, Olivia; Duan, Hongzhe; Wu, Deqing; Akushevich, Igor; Stallard, Eric; Kulminski, Alexander; Christensen, Kaare; Feitosa, Mary F.; O’Connell, Jeffrey R.; Parker, Daniel; et al. (Frontiers in Genetics, 2023)
Dysregulation of physiological processes may contribute to Alzheimer’s disease (AD) development. We previously found that an increase in the level of physiological dysregulation (PD) in the aging body is associated with declining resilience and robustness to major diseases. Also, our genome-wide association study found that genes associated with the age-related increase in PD frequently represented pathways implicated in axon guidance and synaptic function, which in turn were linked to AD and related traits (e.g., amyloid, tau, neurodegeneration) in the literature. Here, we tested the hypothesis that genes involved in PD and axon guidance/synapse function may jointly influence onset of AD. We assessed the impact of interactions between SNPs in such genes on AD onset in the Long Life Family Study and sought to replicate the findings in the Health and Retirement Study. We found significant interactions between SNPs in the UNC5C and CNTN6, and PLXNA4 and EPHB2 genes that influenced AD onset in both datasets. Associations with individual SNPs were not statistically significant. Our findings, thus, support a major role of genetic interactions in the heterogeneity of AD and suggest the joint contribution of genes involved in PD and axon guidance/synapse function (essential for the maintenance of complex neural networks) to AD development.